2019
DOI: 10.1161/strokeaha.118.022516
|View full text |Cite
|
Sign up to set email alerts
|

Higher Pulsatility in Cerebral Perforating Arteries in Patients With Small Vessel Disease Related Stroke, a 7T MRI Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 28 publications
4
87
2
1
Order By: Relevance
“…Higher cerebral pulsatility index has been shown to be associated with MRI features of cerebral small vessel disease (131) and cognitive impairment (132). Furthermore, a recent study using intravoxel incoherent motion MRI found that the microvascular properties of the hippocampus are altered in individuals with T2D (130), which may be related to worse cognitive function.…”
Section: Methods For Measuring Pulsatility In the Microvasculaturementioning
confidence: 99%
“…Higher cerebral pulsatility index has been shown to be associated with MRI features of cerebral small vessel disease (131) and cognitive impairment (132). Furthermore, a recent study using intravoxel incoherent motion MRI found that the microvascular properties of the hippocampus are altered in individuals with T2D (130), which may be related to worse cognitive function.…”
Section: Methods For Measuring Pulsatility In the Microvasculaturementioning
confidence: 99%
“…An alternative is vasomotion generated by larger, spontaneous, low-frequency contractions and dilations of smooth muscle cells 55,56 , and a role for this motive force is supported by accumulating evidence 54,57 . Additional studies are needed to unravel the contributions of arterial pulsations and vasomotion 58 , and advances in contrast-enhanced MRI could improve visualization of clearance pathways in humans in vivo 59,60 , an important development towards translating experimental observations to the clinical setting.…”
Section: Aβ Clearance Pathwaysmentioning
confidence: 99%
“…Direct imaging of the small penetrating vessels on MRI remains challenging, especially at routinely used field strengths. Although ultra-high field MRI at 7-T (and above) holds the potential to characterize small vessels both in structure and function (96,97), most neuroimaging manifestations captured by MRI are parenchymal alterations thought to arise from small vessel pathology. A detailed overview of the broad spectrum of SVD-related lesions together with consensus terminology has been provided by the STRIVE (STandards for ReportIng Vascular changes on nEuroimaging) initiative (95).…”
Section: Imagingmentioning
confidence: 99%